Legal Aspects of Inheritance in the Batak community in Parapat - Imman Yusuf Sitinjak; Humala Sitinjak (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to determine how the implementation of in heritance that occurs and the problems that often occur with inheritance in the Batak community in Parapat. Inheritance is not a problem if it is carried out in accordance with the provisions of the division of inheritance, and the division of inheritance is carried out by mutual agreement. However, currently there are many problems that occur when inheritance is not carried out evenly, and it is not uncommon for inheritance to become a dispute for each heir. This study discusses the implementation of community inheritance in Parapat as well as the problems that often occur in the implementation of inheritance and the problem of transferring inheritance rights to the Batak community in Parapat. In the Parapat community, the dominant ethnicity is the Batak, most of them carry out inheritance by dividing the inheritance of customary law. The implementation of the division of inheritance is by focusing on boys as heirs, while for girls it is only limited to "Lean-lean = or commonly called gifts from male heirs". At the time of transferring the inheritance as the right of the heirs, there are many obstacles for the heirs to control their rights, due to the existence of heirs who make it difficult by not recognizing the rights of the other heirs according to their share. When you want to take over, you need the heirs, both boys and girls, to sign. However, when other heirs often do not want to recognize the rights of other heirs, it makes it difficult for other heirs to claim or transfer their rights as traditional owners of the inheritance. Therefore it is important in the implementation of customary inheritance in Parapat, the heirs make a certificate of inheritance rights and also a power of attorney to be able to transfer the rights of the inheritance. Because when later the heirs do not want to recognize or sign for the transfer of rights, the existence of such a power of attorney will not make it difficult for the other heirs to transfer their respective rights in the customary inheritance.